SELF-REPRESENTATION IN SOCIAL MEDIA (DRAMATURGY STUDIES OF DRUG-USING ARTISTS) - Almaidah, Anata Reyustina; Harianto, Sugeng (Universitas Tanjungpura, 2023)
Social media is one of the most existing online media used today by all groups, including artists. The existence of social media is used to support his popularity and good image in front of the public. These artists try. However, the lives of these artists are sometimes inversely proportional to their real lives, this also happened to one of the artists, namely Ardhito Pramono. This research uses data collection techniques in the form of literature studies, which are then analyzed using the Miles and Huberman techniques. The theory used in this research is Erving Goffman's dramaturgical theory. In dramaturgical theory, it is explained that in an effort to achieve a goal, a person will carry out various actions that can create a good impression of other people towards him, so that the terms front stage and backstage appear. This research produces a finding that the life of artist Ardhito Pramono is in accordance with dramaturgical theory, where there is a front stage and a backstage. On the front stage, Ardhito displays his good image through his social media by managing his appearance and creating songs that can inspire other people, especially teenagers. Meanwhile, in the backstage, Ardhito is a drug user, whose drug use is considered deviant behavior in society.